Homocysteine, Cortisol, Diabetes Mellitus, and Psychopathology. (1st February 2015) - Kontoangelos, K.; Papageorgiou, C. C.; Raptis, A. E.; Tsiotra, P.; Lambadiari, V.; Papadimitriou, G. N.; Rabavilas, A. D.; Dimitriadis, G.; Raptis, S. A.
Abstract : Objective . This study investigates the association of homocysteine and cortisol with psychological factors in type 2 diabetic patients. Method . Homocysteine, cortisol, and psychological variables were analyzed from 131 diabetic patients. Psychological factors were assessed with the Eysenck Personality Questionnaire (EPQ), Hostility and Direction of Hostility Questionnaire (HDHQ), the Symptom Checklist 90-R (SCL 90-R), the Zung Self-Rating Depression Scale (ZDRS), and the Maudsley O-C Inventory Questionnaire (MOCI). Blood samples were taken by measuring homocysteine and cortisol in both subgroups during the initial phase of the study ( T 0). One year later ( T 1), the uncontrolled diabetic patients were reevaluated with the use of the same psychometric instruments and with an identical blood analysis. Results . The relation of psychoticism and homocysteine is positive among controlled diabetic patients ( P value =0.006 < 0.05 ) and negative among uncontrolled ones ( P value = 0.137). Higher values of cortisol correspond to lower scores on extraversion subscale( r p = - 0.223, P value = 0.010). Controlled diabetic patients showed a statistically significant negative relationship between homocysteine and the act-out hostility subscale( r sp = - 0.247, P = 0.023 ) . There is a statistically significant relationship between homocysteine and somatization( r sp = - 0.220, P = 0.043 ) . Conclusions . These findings support the notion that homocysteine and cortisol are related to trait and state psychological factors in patients with diabetes mellitus type 2.